THE EFFECTIVENESS OF THINKING ALOUD STRATEGY IN ACHIEVING AND DEVELOPING REASONING THINKING AMONG THE SECOND YEAR MIDDLE SCHOOL STUDENTS IN MATHEMATICS - Dr. Haider Abdul Kareem Mohsen Al-Zuhairy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of the research was to identify (the effectiveness of thinking aloud strategy in achievement and the development ofreasoning thinking. among students of secondary school in the. second grade in mathematics). The sample consisted of (63) intermediate second-grade students in Ramadi - Anbar Governorate for the academic year 2017-2018 They were divided into two. groups: experimental with (32) students, and. control with (31) students. The researcher prepared an achievement test consisting of (40) objective items of (multiple choice) types with four alternatives, and also a test of reasoning thinking consisting of (30) items distributed equally on the skills (induction and deduction) four alternatives in each item. Those two tests were checked for their reliability.